Changes in soil microbial community and activity in warm temperate forests invaded by moso bamboo (Phyllostachys pubescens). Issue 5 (1st October 2016) - Wang, Xin; Sasaki, Akiko; Toda, Motomu; Nakatsubo, Takayuki
Abstract: In the past few decades, moso bamboo ( Phyllostachys pubescens ) forests in Japan have rapidly expanded, and moso bamboo is now invading nearby native forests. In this study, we assessed the effects of moso bamboo invasion on the soil microbial community and activity in warm temperate forests in western Japan. We sampled soil, measured soil microbial respiration, and used phospholipid fatty acid (PLFA) analysis to examine changes in microbial community composition. We found that the invasion of bamboo into the native secondary forest of Japan can cause changes to some soil properties. We also observed a significant difference in soil microbial community composition between the bamboo and native forests. The ratio of bacterial PLFA to fungal PLFA was significantly higher after bamboo invasion, while bacterial PLFA contents were significantly lower in the organic layer. Soil microbial respiration rates significantly decreased in the organic layer, and significantly increased in the mineral layer. Microbial respiration activity, as indicated by soil microbial respiration rates per total PLFA content, decreased in the organic layer but increased in the mineral layer after bamboo invasion. These results indicate that bamboo invasion significantly affects associated soil microbial communities and decomposition patterns of soil organic matter.